2010
DOI: 10.1261/rna.1962010
|View full text |Cite
|
Sign up to set email alerts
|

Bunyamwera virus can repair both insertions and deletions during RNA replication

Abstract: The genomic termini of RNA viruses contain essential cis-acting signals for such diverse functions as packaging, genome translation, mRNA transcription, and RNA replication, and thus preservation of their sequence integrity is critical for virus viability. Sequence alteration can arise due to cellular mechanisms that add or remove nucleotides from terminal regions, or, alternatively, from introduction of sequence errors through nucleotide misincorporation by the error-prone viral RNAdependent RNA polymerase (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This strategy would seem risky, given the functional sensitivity of terminal promoter sequences and the cellular response to dsRNA. However, BUNV is known to be able to repair partial deletions at its termini that could arise through nuclease attack (54), thus restoring wild-type sequence and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy would seem risky, given the functional sensitivity of terminal promoter sequences and the cellular response to dsRNA. However, BUNV is known to be able to repair partial deletions at its termini that could arise through nuclease attack (54), thus restoring wild-type sequence and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the mechanism behind the regain of fitness, the entire nucleotide sequences of a number of viral genomes were determined to assess the extent of mutation. A previous in vitro study using a minigenome system showed that BUNV was able to repair both insertions and deletions in its UTRs (28). Therefore, the first concern was to ensure that the UTRs were unchanged and the deletions were still present after 10 passages.…”
Section: Discussionmentioning
confidence: 99%
“…Walter and Barr recently discovered that the RdRp of BUNV is capable of correcting sequence alternations to the NTRs (Walter and Barr 2010 ) . When an intact NTR was introduced into the antigenomic 3 ¢ end, it was precisely removed, and the impaired RNA synthesis that resulted from the NTR addition was restored.…”
Section: Viral Rna Replicationmentioning
confidence: 99%
“…Likewise, when nucleotides were deleted from the antigenomic 3 ¢ end and replaced with a duplicate and intact NTR, the inserted NTR was removed and the missing nucleotides were reinstated. Furthermore, Walter and Barr demonstrated that the repair of NTRs is likely accomplished by direct entry of the RdRp into the internal NTRs during replication (Walter and Barr 2010 ) . However, the precise repair mechanism employed by RdRp remains unclear at this point.…”
Section: Viral Rna Replicationmentioning
confidence: 99%